Efektivitas Model Pembelajaran Small Group Discussion (SGD) dalam Meningkatkan Kemampuan Literasi Ekonomi Syariah Mahasiswa (Studi di Institut Agama Islam Negeri Ponorogo) - Mohammad Jauharul Arifin; Ilham Cahyanto; Nadia Ulfa'ngin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
Currently, the development of the Islamic economy in Indonesia is quite rapid. This is indicated by the results of the Global Islamic Economy Indicator Score (GIEI) survey in 2019-2020, where Indonesia was ranked 5th with a value of 49, right below the country of Saudi Arabia with a score of 50.This must be accompanied by Islamic economic literacy from young people especially. To create a young generation who has good Islamic economic literacy, it is necessary to have learning innovations. For this reason, the researchers conducted research related to the small group discussion learning model in increasing student economic literacy. This study uses a qualitative approach with descriptive analysis. This research results that the small group discussion learning model can improve students' Islamic economic literacy. This can be seen from the comparison between the pretest and posttest results. Where before the SGD treatment, as many as 43% of students got a C, but after the treatment experienced a decrease to 20%. For students who got an A score, it increased where before treatment was 7%, after treatment it increased to 13%.